Programmable integrated photonics - Capmany, José (Professor in Photonics and Optical Communications); Pérez, Daniel (Oxford University Press, 2020)
This is the first comprehensive, self-contained introduction to the emergent field of Programmable Integrated Photonics. It covers theoretical and practical aspects ranging from basic technologies and the building of photonic component blocks, to design alternatives and principles of complex programmable photonic circuits, and their applications.